Model Politik Pembangunan Organisasi Kemasyarakatan Islam Muhammadiyah dan Al Washliyah di Kota Medan - Kusmanto, Heri; Warjio, Warjio (JPPUMA Jurnal Ilmu Pemerintahan dan Sosial Politik Universitas Medan Area, 2018)
This study discusses the political model of development of Islamic community organizations namely Muhammadiyah and Al-Washliyah in Medan City. Specifically, this study describes the politics of development of Islamic community organizations (Muhammadiyah and Al-Washliyah) in maintaining and developing their existence in development activities in Medan City. The context of the research carried out mainly concerns the orientation of the two Islamic community organizations which are known to have different schools of thought from each other, Muhammadiyah represents modern thought while Al-Washliyah represents traditional circles in the context of their development activities in Medan City. This study examines the form or model and strategy of development, as well as the direction or orientation that forms the basis of Muhammadiyah and Al-Washliyah's political development policies in Medan City, which of course will have differences because of the different schools of thought. In addition, of course, the development of directions or orientations that shape the political model of development will also have a system or a different way from what has been developed by the government which tends to develop with a secular approach that is felt to have a community side on one side poverty, inequality and moral degradation.